Oil Spill Preparedness and Response in the Arctic. The effect of low temperature on oil spill response operations in the Arctic with respect to overall equipment effectiveness - Rolandsen, Markus Helfjord (UiT The Arctic University of Norway, 2018)
Effectiveness is an important term in oil spill response operations. Literature often relate to the level of effectiveness connected to either mechanical containment and recovery, in-situ burning or chemical dispersant application. The term effectiveness in oil spill response operations can be related to existing theory and the perspective of Overall Equipment Effectiveness (OEE). The perspective of OEE can further be related to the perspective of Reliability, Availability, and Maintainability (RAM). This research study will review the effect of low temperature on oil spill response operations in the Arctic through a literature study. The literature study will cover research related to oil spill response operation in the Arctic and evaluate the effectiveness in general terms. Further in the literature study, the approach to effectiveness in oil spill response operations is discussed. Based on this discussion and on existing theory of OEE and RAM, it is found clear relevance in evaluating the effect of low temperature on RAM performance in oil spill response operations. To evaluate the effect of low temperature on RAM performance in oil spill response operations, existing literature and research covering RAM performance of oil and gas production facilities in the Arctic was reviewed, along with research covering oil spill response operations and Arctic operations in general. This literature review, with its focus on low temperature as influencing factor, has led to some suggested aspects for improving RAM performance of oil spill response operations in the Arctic. These aspects for improvement are alleged to substantiate the OEE of oil spill response operations.